Pregnancy in Patients with Low Back Pain - Seddighi, Afsoun; Sedighi, Amirsaeed; Jamshidi, Shiva; Rahimi Baghdashti, Hesam (International Clinical Neuroscience Journal, 2019)
Pregnancy-related lumbopelvic pain has been a serious and common problem since ancient time. The present review article focuses on terminology, types, clinical presentation, and management of these problems. There are two entities regarding pregnancy-related lumbopelvic pain: pelvic girdle pain (PGP)’’, and pregnancy-related low back pain (PLBP). There are multiple mechanisms behind these disabilities. Age, multiparty, heavy weight lifting, hard physical activity, previous low back pain, and low education increase the prevalence. About one-half of women with pregnancy-related lumbopelvic pain have PGP, one-third LBP, and one-sixth have both conditions. Overall, the literature reveals that PPP deserves serious attention from the clinical and economic standpoints